Thirty Years On: Labour Market Deregulation and its Aftermath in New Zealand and the United Kingdom - Deakin, Simon (Victoria University of Wellington Law Review, 2019)
Gordon Anderson has made enduring contributions to two linked strands of labour law scholarship: analysis of the impact on labour law on policies of deregulation, and the study of labour law as a mechanism for constituting and structuring the labour market. This article considers the prospects for labour law reform in New Zealand and the United Kingdom in the light of scholarship on these issues since the 1980s. It argues that a return to a more worker-protective labour law in these countries is feasible despite the legacy of the deregulatory changes of the 1980s and 1990s. Fundamental changes in labour laws are not brought about by legal scholarship, but, as in the 1980s, an economically-informed analysis of the operation of labour laws could make a difference to the next wave of reforms.